A Preliminary Study of Work-Focused Cognitive Behavioural Group Therapy for Japanese Workers. Issue 2 (6th June 2018) - Ito, Daisuke; Watanabe, Asuka; Takeichi, Sakino; Ishihara, Ayako; Yamamoto, Kazuyoshi
Abstract : Background: In Japan, cognitive behavioural therapy (CBT) has been introduced in the 'Rework Programme', but its impact on return to work (RTW) has not been fully clarified.Aims: This pilot study investigated the initial efficacy of a work-focused cognitive behavioural group therapy (WF-CBGT) for Japanese workers on sick leave due to depression.Method: Twenty-three patients on leave due to depression were recruited from a mental health clinic. WF-CBGT including behavioural activation therapy, cognitive therapy, and problem-solving therapy techniques was conducted for eight weekly 150-minute sessions. Participants completed questionnaires on depression and anxiety (Kessler-6), social adaptation (Social Adaptation Self-Evaluation Scale), and difficulty in RTW (Difficulty in Returning to Work Inventory) at pre- and post-intervention time points. Rates of re-instatement after the intervention were examined.Results: One participant dropped out, but 22 participants successfully completed the intervention. All scale scores significantly improved after intervention and, except for difficulty in RTW related to physical fitness, all effect sizes were above the moderate classification. All participants who completed the intervention succeeded in RTW.Conclusions: Results suggested the possibility that WF-CBGT may be a feasible and promising intervention for Japanese workers on leave due to depression regardless of cross-cultural differences, but that additional research examining effectiveness using controlled designs and other samples is needed. Future research should examine the efficacy of this programme more systematically to provide relevant data to aid in the continued development of an evidence-based intervention.